Integrin endosomal signalling suppresses anoikis - Alanko, Jonna (Nat Cell Biol, 2015)
Integrin containing focal adhesions (FAs) transmit extracellular signals across the plasma membrane to modulate cell adhesion, signalling and survival. Although integrins are known to undergo continuous endo/exocytic traffic, potential impact of endocytic traffic on integrin-induced signals is unknown. Here, we demonstrate that integrin signalling is not restricted to cell-ECM adhesions and identify an endosomal signalling platform that supports integrin signalling away from the plasma membrane. We show that active focal adhesion kinase (FAK), an established marker of integrin-ECM downstream signalling, localises with active integrins on endosomes. Integrin endocytosis positively regulates adhesion-induced FAK activation, which is early endosome antigen-1 (EEA1) and small GTPase Rab21 dependent. FAK binds directly to purified endosomes and becomes activated on them, suggesting a role for endocytosis in enhancing distinct integrin downstream signalling events. Finally, endosomal integrin signalling contributes to cancer-related processes such as anoikis resistance, anchorage-independence and metastasis. Integrins are heterodimeric cell surface adhesion receptors functioning as integrators of the extra-cellular matrix (ECM) driven cues, the cellular cytoskeleton and the cellular signalling apparatus 1.Upon adhesion, integrins trigger the formation of plasma-membrane proximal large mechanosensing and signal-transmitting protein clusters depicted as “adhesomes” 2, 3. In addition, integrins undergo constant endocytic traffic to facilitate focal adhesion turnover, cell migration, invasion and cytokinesis 4. For other receptor systems it is well established that endocytic membrane traffic regulates bioavailability of cell-surface molecules and therefore the intensity and/or specificity of receptor-initiated signals 5, 6. Although active integrins and their ligands have been detected in endosomes 7–9 and increased integrin recycling to the plasma membrane contributes to enhanced signalling of co-trafficked receptor tyrosine kinases10, 11 it has remained unclear whether endocytosed active integrins signal in endosomes. Here, we demonstrate that integrin signalling is not restricted to focal adhesions as previously described and that endocytosis is necessary for full ECM-induced, integrin mediated ERK, AKT and FAK signalling. We find that FAK binds directly to and can become activated on purified endosomes. Moreover, the FERM-domain of FAK is able to bind purified integrin containing endosomes, suggesting the potential for integrin signalling complexes to assemble on endosomes after internalization of active integrins. Importantly, FAK is required for anchorage-independent growth and suppression of anoikis 12. Integrin endosomal signalling correlates with reduced anoikis sensitivity in normal cells and anchorage-independent growth and metastasis in breast cancer cells.